Sistem Ritual Ngiringang Ida Bhatara Pengulu Mesucian di Pura Labuhan Aji pada Masyarakat Catur Desa Adat Dalem Tamblingan - Agus Aditya Saputra; I Gede Suwindia; I Nyoman Miarta Putra (Jayapangus Press, 2026)
The Ngiringang Ida Bhatara Pengulu Mesucian ritual is a sacred tradition practiced by the Catur Desa Adat Dalem Tamblingan community in Buleleng Regency, Bali. This ritual reflects the community's belief in the sanctity of water as the source of life, a medium of purification, and a manifestation of divine power that sustains the balance of nature. This study aims to analyze the reasons for performing the ritual, describe its ritual system, and examine its implications for the community. The research employed a qualitative approach from religious and cultural perspectives. Data were collected through observation, interviews, documentation, and literature review, and were analyzed using descriptive qualitative methods. The findings reveal that the ritual is grounded in theological beliefs regarding the sacredness of water and the existence of Ida Bhatara Pengulu as the guardian of cosmic balance. The ritual system consists of four stages: preparation, the Ngiringang procession, the Mesucian purification ceremony, and communal prayers involving both upstream and downstream communities as an integrated spiritual entity in maintaining harmony. The ritual affirms the sacred value of water as a vital source of life that must be preserved while strengthening the relationship between humans, God, fellow human beings, and nature. Its implications include the enhancement of sraddha (faith) and bhakti (devotion), the reinforcement of social solidarity among the Catur Desa Adat Dalem Tamblingan community, and the development of collective awareness regarding water resource conservation and environmental sustainability. This study concludes that the Ngiringang Ida Bhatara Pengulu Mesucian ritual is not merely a ceremonial activity but a ritual system embodying theological, philosophical, social, and ecological values that remain relevant to supporting the sustainability of community life.